Constitutive and herbivore‐induced plant defences regulate herbivore population processes. Issue 7 (1st May 2019) - Kersch‐Becker, Mônica F.; Thaler, Jennifer S.
Abstract: Herbivore‐induced plant defences regulated by the phytohormones jasmonic acid (JA) and salicylic acid (SA) are predicted to influence herbivore population dynamics, in part because they can operate in a density‐dependent manner. While there is ample evidence that herbivore‐induced plant responses affect individual performance and growth of herbivores, whether they scale‐up to regulate herbivore population dynamics is still unclear. We evaluated the consequences of variation in plant defences and herbivore density on herbivore development, reproduction and density‐dependent population growth. We investigated potential mechanisms affecting the strength of herbivore density‐dependent processes by manipulating jasmonate expression, quantifying plant defensive traits (phytohormones JA and SA and serine proteinase inhibitors) and adding aphids ( Macrosiphum euphorbiae ) at different densities to plants to simulate different initial population density and herbivore load. We manipulated jasmonate defences by using genetically modified lines of tomato plants ( Solanum lycopersicum ) with elevated or suppressed jasmonate‐dependent defences. Jasmonate‐insensitive plants cannot induce the defences regulated by the JA pathway, while jasmonate‐overexpressing plants constitutively express jasmonate‐dependent defences. We found that jasmonate defences provided resistance against aphids and influenced density‐dependent processes. Jasmonate‐overexpressing plants reduced aphid reproduction, prolonged developmental time, dampened aphid populations across all aphid densities and caused density‐independent aphid population growth. Jasmonate‐overexpressing plants showed high JA‐dependent constitutive levels of resistance and were unable to activate the SA pathway in response to aphid feeding. In contrast, jasmonate‐insensitive plants increased aphid reproduction, shortened developmental time, reduced population growth only at high initial densities and promoted strong negative density‐dependent population growth. Aphid feeding on jasmonate‐insensitive plants did not induce jasmonate‐dependent defences, but induced the SA pathway in a density‐dependent manner, which resulted in negative density‐dependent aphid population growth. Aphid feeding on jasmonate‐insensitive and jasmonate‐overexpressing plants differentially activated the salicylate pathway, revealing a negative crosstalk between the defensive phytohormones JA and SA. By muting or enhancing jasmonate‐mediated responses and quantifying SA phytohormone induction, we demonstrated that plant defences are a key factor driving not only the performance, but also the density dependence processes and population growth of herbivores. Abstract : By overexpressing or muting jasmonate‐mediated responses and quantifying salicylic acid phytohormone induction, this study demonstrates that plant defences are a key factor driving not only the performance, but also density dependence processes and population growth of herbivores.